THE SILENT KILLER – OBESITY AND HYPERTENSION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, KELANTAN, June 2015 Both obesity and hypertension (high blood pressure) are widely known as a silent killer that is common among Malaysians because both these diseases are fatal if their effects are taken lightly.